Status of age-friendly city indicators in Iran cities: a systematic review - Fallahi, Fatemeh; Adib-hajbaghery, Mohsen; Safa, Azade (BMC geriatrics, 2024)
The global phenomena of an increasing older population within the total population and the rise in urban older residents have prompted numerous studies on the indicators of an age-friendly city in various Iranian cities. The insights obtained from these studies can aid policymakers in promoting social justice for older adults. Thus, this study aimed to investigate the status of age-friendly city indicators across different cities in Iran. A systematic review was conducted by searching for studies in Persian and English databases until March 2024, including Pubmed, Web of Science, Scopus, Cochrane, Google Scholar, and ScienceDirect, using keywords such as "age-friendly", "elderly-friendly", "cities", "older adults", "aging", "elderly", "indicators", "components", "criteria", "features", "characteristics", "indexes", "Iran", and "urban space", along with their MeSH equivalents, employing "AND" and "OR" operators. Additionally, Persian databases such as Magiran and SID were extensively searched using keywords like "elderly-friendly", "city", "urban spaces", "Iran", "indicators", "components", "features", and "criteria". The references of the final articles were also examined to ensure search accuracy. The results from the studies on the indicators of an age-friendly city were reviewed, summarized, and ultimately reported. The initial search yielded 2857 articles, of which 34 were included in the systematic review. Only two studies addressed the indicators based on the needs of the older adults, with the majority reporting unfavorable urban conditions for the older adults. Despite these unfavorable conditions, the index of open spaces and buildings received the highest rank among the examined indicators. However, two indicators-respect for older adults, social acceptance, civic participation, and employment- did not perform well in any study. The findings indicated that Iran failed to meet the required standards for age-friendly cities. Therefore, it is recommended that policymakers in the field of geriatric health take measures to identify and mitigate environmental risk factors for older adults. This systematic review was registered on the Prospero database with the number CRD42023475657 on date 8 November 2023.